2000
DOI: 10.1054/bjoc.2000.1110
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status and risk of adenocarcinoma of the oesophagus and cancer of the gastric cardia in Scotland

Abstract: The incidence of oesophageal adenocarcinoma and gastric cardia cancer is rising in many countries and the observed increases are not believed to be explained wholly by changes in diagnostic or reporting practices (Devesa and Fraumeni, 1999). The risks of cancers of the oesophagus (ICD-9 150) and stomach (151) have been correlated strongly with socioeconomic indicators, both in Scotland (Harris et al, 1998) and elsewhere (Faggiano et al, 1997). However, it has been argued that the existing international classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
34
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 16 publications
(14 reference statements)
10
34
0
Order By: Relevance
“…We also observed that high income and high degree of education were protective factors of gastric cardia cancer, which was consistent with the studies more than 10 years ago (Brewster et al, 2000;Sun et al, 2002). Low socio-economic status and poor education were still the key factors on the life style and dietary structure for the rural resident in Linzhou.…”
Section: Discussionsupporting
confidence: 93%
“…We also observed that high income and high degree of education were protective factors of gastric cardia cancer, which was consistent with the studies more than 10 years ago (Brewster et al, 2000;Sun et al, 2002). Low socio-economic status and poor education were still the key factors on the life style and dietary structure for the rural resident in Linzhou.…”
Section: Discussionsupporting
confidence: 93%
“…The present study used two measures of socioeconomic status, the Townsend score based on the 1991 census using regional quintiles and the IMD 2004 using national quintiles based on 2001 data, with almost identical results, showing there was no association between socioeconomic status and EAC. Thus it is unlikely that deprivation or affluence contributes to the development of EAC in England, in keeping with findings in Scotland from 1987 to 1996 [17].…”
Section: Easr Per 100000supporting
confidence: 73%
“…A direct comparison of ESCC and EAC in Australia suggests ESCC is more clearly associated with deprivation [16]. The influence of socioeconomic status upon the incidence of EAC has yet to be examined in England, although no association was found in Scotland [17].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, body mass index seems to be inversely related to the risk of oesophageal squamous cell carcinoma. The influence of obesity on oesophageal adenocarcinoma and gastric cardia adenocarcinoma may be related to higher incidence of gastroesophageal reflux in obese persons, since the risk of gastroesophageal reflux is strongly related to the risk for Barrett's oesophagus [34][35][36][37]. Tobacco smoking is a strong risk factor for oesophageal squamous cell carcinoma, but is only a weak risk factor for oesophageal adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%